Revalorización de la cocina tradicional del cantón Cotacachi parroquia rural Quiroga provincia de Imbabura, a través de un catálogo digital - Casa Vera, María Fernanda (2023)
This research article aims to achieve the objective of revaluing the traditional cuisine of the Quiroga parish, Cotacachi canton, through the creation of a digital catalog in order to preserve the local food heritage. The methodology in this research adopts a mixed approach. It contributes to the explanatory study through a quantitative survey of 10 closed questions applied to the parish of Quiroga in the Cotacachi canton. In addition, a qualitative approach was carried out with a semi-structured interview of 10 open questions with 4 people from the Quiroga parish. Next, it was possible to obtain the calculation of the sample with the PEA of the Quiroga parish, which is 6454, resulting in the application of 67 surveys. Several traditional dishes and drinks were identified that are no longer consumed as before, one of them are potatoes with watercress and morocho as a drink, as well as condiments no longer used as before, annatto grains. Furthermore, another relevant result on the part of the residents is that the knowledge is continued to future generations without losing the homely touch. In conclusion, the research identifies the prevailing need to collect and record this invaluable intangible heritage such as the traditional dishes of Quiroga.